2018
DOI: 10.1093/brain/awy152
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between spinal cord and cerebral cortex metabolism in amyotrophic lateral sclerosis

Abstract: Using a computational approach to extract the spinal canal from whole-body PET/CT images, Marini et al. reveal increased glucose consumption in the spinal cord in prospectively recruited patients with amyotrophic lateral sclerosis. Simultaneous measurement of brain 18F-Fluorodeoxyglucose uptake reveals a divergent metabolic response in the two structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…Accordingly, the SUVmax of the [12,13]. While a pattern of decreased or increased [ 18 F]FDG uptake was observed in in ammatory myelopathies and neurosarcoidosis, presumably re ecting varying delay between disease onset and time of PET and possible interference with steroid therapy [12,13], in case of amyotrophic lateral sclerosis elevated [ 18 F]FDG uptake values were reported [24]. Additional potential diseases suitable to be evaluated with PET of the spinal cord include trauma, post-radiation myelopathy, Vitamin B12 de ciency myelopathy and some neurodegenerative diseases which primarily affect the spinal cord as Friedreich's ataxia and hereditary spastic paraplegia.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the SUVmax of the [12,13]. While a pattern of decreased or increased [ 18 F]FDG uptake was observed in in ammatory myelopathies and neurosarcoidosis, presumably re ecting varying delay between disease onset and time of PET and possible interference with steroid therapy [12,13], in case of amyotrophic lateral sclerosis elevated [ 18 F]FDG uptake values were reported [24]. Additional potential diseases suitable to be evaluated with PET of the spinal cord include trauma, post-radiation myelopathy, Vitamin B12 de ciency myelopathy and some neurodegenerative diseases which primarily affect the spinal cord as Friedreich's ataxia and hereditary spastic paraplegia.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported a predictive power of spinal cord [18F]-uorodeoxyglucose (FDG) uptake computationally extracted from PET/CT images of ALS patients [7]. The apparent metabolic activation of this nervous district faced an opposite pattern in the brain cortex that showed a generalized reduction in tracer uptake [8]. By contrast, it extended to the psoas muscles of the same patients, suggesting a link between the metabolic pattern of the second motoneuron and its effector [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, evidence points to a defective carbohydrate metabolism in ALS. Studies using [ 18 F]-2-fluoro-2-deoxy-D-glucose positron emission tomography (PET) reported that cortical glucose uptake is reduced in ALS patients while local glucose uptake seems to be increased in both the cervical and dorsal spinal cord [38][39][40]. Furthermore, cortical hypometabolism is suggested to be an early diagnostic event that can be linked to the severity of the disease [38,41].…”
Section: Introductionmentioning
confidence: 99%